2023
DOI: 10.4330/wjc.v15.i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibrinogen, albumin and fibrinogen to albumin ratio in determining angiographic severity and outcomes in acute coronary syndrome

Abstract: BACKGROUND Coronavirus disease 2019 (COVID-19) pandemic unmasked the huge deficit in healthcare resources worldwide. It highlighted the need for efficient risk stratification in management of cardiovascular emergencies. AIM To study the applicability of the old, available and affordable nonconventional biomarkers: albumin and fibrinogen in their ability to predict angiographic severity and clinical outcomes in patients with acute coronary syndrome (ACS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The level of albumin in the survivors and non-survivors was statistically significantly lower by 18 and 27%, respectively, relative to the control, whereas for the total protein, a statistically significant decrease of 11% was noted only for the group of deceased patients. This indicates, firstly, the critical role of albumin in the outcome of the disease and the high significance of this indicator for future risk stratification, which is confirmed by numerous data from other researchers [ 18 , 22 , 46 , 53 ], and secondly, the preservation of the protein-synthesizing function of the liver in patients with a negative prognosis, and even some increase in it, mainly due to the synthesis of CRP when stimulated by pro-inflammatory cytokines [ 60 ]. The esterase activity of albumin does not undergo significant changes, while the activity of PON1 in both groups of COVID-19 patients, regardless of the outcome, significantly decreases by 35%.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The level of albumin in the survivors and non-survivors was statistically significantly lower by 18 and 27%, respectively, relative to the control, whereas for the total protein, a statistically significant decrease of 11% was noted only for the group of deceased patients. This indicates, firstly, the critical role of albumin in the outcome of the disease and the high significance of this indicator for future risk stratification, which is confirmed by numerous data from other researchers [ 18 , 22 , 46 , 53 ], and secondly, the preservation of the protein-synthesizing function of the liver in patients with a negative prognosis, and even some increase in it, mainly due to the synthesis of CRP when stimulated by pro-inflammatory cytokines [ 60 ]. The esterase activity of albumin does not undergo significant changes, while the activity of PON1 in both groups of COVID-19 patients, regardless of the outcome, significantly decreases by 35%.…”
Section: Resultssupporting
confidence: 70%
“…Thus, the index [Urea] × [MDA]/(BChEb × [ALB]) can claim to take a place among the most promising indices proposed to date, among which there is none that includes the activity of BChE and at the same time demonstrates such striking differences at the stage of admission to the clinic between survivors and those who died during treatment from COVID-19. At the same time, it should be mentioned that most of the proposed indices include albumin in the denominator: LDH/[ALB], [Lact]/[ALB], [Fibr]/[ALB], [Urea]/[ALB], and [CRP]/[ALB] [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Importantly, correlation analysis independent of age and concomitant pathology showed that the ratio of [CRP]/[ALB] negatively correlates with oxygen saturation (SO 2 ), spirometric indices (FEV1, forced expiratory volume in the first second, and FVC, forced volume capacity) and lung diffusion values (DLCO, carbon monoxide diffusion capacity) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the FAR is associated with an adverse prognosis in many cancers and has been frequently studied in cardiovascular diseases (CVDs), particularly CAD [ 13 , 14 , 16 , 18 , 39 , 40 ]. However, there is no evidence that reducing fibrinogen or correcting hypoproteinaemia can improve the prognosis of CVD, including HF.…”
Section: Discussionmentioning
confidence: 99%
“…MPN inflammation is dependent and independent of the mutational landscape of the disease and is influenced not only by genetics, but also by the immune system, diet, metabolism, and comorbidities[ 59 ]. Furthermore, researchers have pointed out that both MPN patients[ 58 ] and MI subjects have elevated concentrations of ferritin[ 60 , 61 ], C-reactive protein[ 62 , 63 ], and fibrinogen[ 64 ]. Pro-inflammatory cytokines, such as tumor necrosis factor-alpha, interleukin (IL)-6 and IL-1, and the NACHT, LRR, and PYD domains-containing protein 3 inflammasome have been reported to contribute to the pathogenesis of both MI[ 65 - 67 ] and MPN[ 58 , 59 , 68 - 70 ].…”
Section: Future Perspectives: Can We Quest For Biomarkers?mentioning
confidence: 99%